Digital Hardware for Peer Assessment in K-12 Schools and Universities - Topping, Keith James (Frontiers in Education, 2021)
Digital Peer Assessment (PA) is an arrangement for learners to consider and specify the level, value or quality of a product or performance of other equal-status learners, using computers, tablets, mobiles or other devices and the internet. Digital PA is of increasing relevance as more educational establishments move towards online or blended learning. It has been widely used for some time, not only in elementary (primary) schools and high (secondary) schools, but also in higher education. In this paper, the purposes of PA are considered. Then, questions of effectiveness are briefly discussed. Then, the majority of the paper describes in general terms how to do it. A review is offered of the variation in types of PA and the underpinning theory, both of which have practical implications, irrespective of whether the PA is digital or face-to-face. Then, the use of different kinds of digital hardware in different kinds of PA will be considered. After this, the social and emotional aspects of digital PA are considered. As the contexts are so different, differences between primary school, high school and higher education are reviewed. A conclusion summarises the strengths and weaknesses of digital PA, which can certainly be effective as a teaching and learning method and enhance student communication, problem-solving and self-confidence.